A novel instrumented human head surrogate for the impact evaluation of helmets - Petrone, N.; Carraro, G.; Castello, S.D.; Broggio, L.; Koptyug, A.; Bäckström, M. (Proceedings, 2018)
A novel Human Head Surrogate was obtained from available MRI scans of a 50th percentile male human head. Addictive manufacturing was used to produce the skull, the brain and the skin. All original MRI geometries were partially smoothed and adjusted to provide the best biofidelity compatible with printing and molding technology. The skull was 3D-printed in ABS and ten pressure sensors were placed into it. The brain surrogate was cast from silicon rubber in the 3D-printed plastic molds. Nine tri-axial accelerometers (placed at the tops of the lobes, at the sides of the lobes, in the cerebellum and in the center of mass) and a three-axis gyroscope (at the center of mass) were inserted into the silicon brain during casting. The cranium, after assembly with brain, was filled with silicon oil mimicking the cerebral fluid. Silicon rubber was cast in additional 3D-printed molds to form the skin surrounding the cranium. The skull base was adapted to be compatible with the Hybrid-III neck and allow the exit of brain sensors cabling. Preliminary experiments were carried out proving the functionality of the surrogate. Results showed how multiple accelerometers and pressure sensors allowed a better comprehension of the head complex motion during impacts.